2023
DOI: 10.3389/fpubh.2023.1178167
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for SARS-CoV-2 infection during the early stages of the COVID-19 pandemic: a systematic literature review

Matthew Harris,
John Hart,
Oashe Bhattacharya
et al.

Abstract: IntroductionIdentifying SARS-CoV-2 infection risk factors allows targeted public health and social measures (PHSM). As new, more transmissible variants of concern (VoC) emerge, vaccination rates increase and PHSM are eased, it is important to understand any potential change to infection risk factors. The aim of this systematic literature review is to describe the risk factors for SARS-CoV-2 infection by VoC.MethodsA literature search was performed in MEDLINE, PubMed and Embase databases on 5 May 2022. Eligibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Our data are compatible with an explanation that can be modeled with classic utility theory [ 75 ]. At the beginning of the pandemic, the risk carried by catching COVID-19 was high [ 76 ]. Reports of hospitalization, suffering, and death made the disease a terrifying perspective for many [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are compatible with an explanation that can be modeled with classic utility theory [ 75 ]. At the beginning of the pandemic, the risk carried by catching COVID-19 was high [ 76 ]. Reports of hospitalization, suffering, and death made the disease a terrifying perspective for many [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 16 During the pandemic furlough and work from home orders were designed to restrict exposure risk, whilst simultaneously necessitating certain occupations as keyworkers with potential for an increased exposure. Studies investigating keyworker status and inability to work from home have tended to confirm these assumptions, 17 18 however a study of the ONS infection survey reported contradictory results for furlough than the expectation. 19 Some of the restrictions imposed during lockdown have changed working habits over the long-term with a greater proportion of the population working from home or hybrid working.…”
Section: Introductionmentioning
confidence: 99%